Evaluation of the protective effect of Paeonia emodi Wall on rat model of Parkinson’s disease induced by 6 hydroxy dopamine - Jalgaonkar, Sharmila V.; Kamble, Abhay P.; Parmar, Urwashi I.; Kurle, Dnyaneshwar G.; Bedrekar, Moin S.; Gursahani, Malvika (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Generation of reactive oxygen species together with paucity of antioxidant defense is considered as an important cause for dopaminergic neuronal death. Review of literature indicates that none of the drugs so far studied for preventing the PD were found to be promising for use. Therefore, the present study was planned to evaluate the neuroprotective effect of Paeonia emodi Wall (PEW) in 6-hydroxy dopamine induced Parkinson’s disease (PD) model. Methods: The study was conducted on Wistar rats where Parkinson’s disease was induced by producing the striatal 6-hydroxy dopamine lesions. The test animals received ethanolic extract of PEW at dose of 200 and 300mg/kg for 28 days. Circling behavior, spontaneous locomotor activity, muscular coordination and akinesia were studied. Antioxidant levels were assessed by biochemical estimation and histopathology was carried out for dopaminergic neuronal loss. Results: PEW ethanolic extract showed significant dose dependent recovery in number of circlings, line crossing, muscular coordination and akinesia. A significant increase in MDA levels and decreased GSH level in PEW treated groups was observed in test groups as compared to control group (p<0.05). Normal architecture was retained only in PEW 300mg/Kg (p<0.05). L-Dopa did not showed effect on biochemical and histological parameters. Conclusions: The ethanolic extract of PEW showed neuroprotective activity against 6-hydroxy dopamine induced Parkinson’s disease in rats in both 200 and 300mg/kg doses. The protective action of PEW in PD can be because of its ability to reduce the oxidative stress.